Evaluating Stress Monitoring Pipelines at the Ultra-Edge: A Mobile Device-Based Study - Gamero, Vanessa; Kofuji, Sergio T. (Anais do Simpósio Brasileiro de Computação Aplicada à Saúde (SBCAS); 2026: Anais do XXVI Simpósio Brasileiro de Computação Aplicada à SaúdeDO - 10.5753/sbcas.2026.21682, 2026)
Continuous stress monitoring using pervasive sensing generates multimodal data streams that are processed through pipelines, which may be implemented across distributed architectures. In this context, smartphones can operate as ultra-edge nodes, enabling local processing of these data while reducing latency and data transmission to upper layers. However, there is limited empirical analysis of how these pipelines operate under continuous execution at the ultra-edge. This study addresses this gap by evaluating the feasibility of executing a stress monitoring pipeline at the ultra-edge through the quantification of its data volume and computational requirements under continuous execution. For this purpose, each pipeline stage is analyzed in terms of generated data volume and the associated computational requirements in CPU, memory, and energy usage. A baseline configuration is compared with alternative strategies to reduce data volume and computational load. Preliminary results show that input data rates are low; however, continuous processing introduces sustained computational demands that must be considered for real-world use. These results provide a baseline for evaluating processing costs in subsequent pipeline stages.